Mama, were you ever young? - Hay, John Williams; Cline, Paul; Sieck, Judythe (San Diego : Green Tiger Press, 1989)
A mother explores with her children the time when she herself was young and explains the ways in which she remains young.
"Childrens Press choice reinforced binding"--P. [4] of cover.
Keywords: Mother and child -- Fiction; Stories in rhyme